2016
DOI: 10.25011/cim.v39i6.27506
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of MACC1 Gene Expression in Head and Neck Cancer and Cancer Stem Cells

Abstract: Purpose: By investigating the MACC1 gene (metastasis-associated in colon cancer 1) in cancer stem cells (CSC) resistant to chemotherapy and in cancer stem cells (CSC) resistant to chemotherapy and in cancer cells (CS) sensitive to chemotherapy we determineda steady expression in both types of cells in head and neck cancer. In conformity with the result we examined if this gene could be a competitor gene for chemotherapy. According to literature, the MACC1 gene shows a clear expression in head and neck cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…50 MACC1 is considered the main regulator of tumor progression in TSCC, in which it affects a number of malignant processes. 33,50 MACC1 affected cancer progression through different mechanisms. For example, MACC1 improves the cisplatin resistance partially in lung cancer via the PI3K/AKT pathway, 51 whereas its depletion suppresses lung cancer cell proliferation and causes cell apoptosis through the β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 MACC1 is considered the main regulator of tumor progression in TSCC, in which it affects a number of malignant processes. 33,50 MACC1 affected cancer progression through different mechanisms. For example, MACC1 improves the cisplatin resistance partially in lung cancer via the PI3K/AKT pathway, 51 whereas its depletion suppresses lung cancer cell proliferation and causes cell apoptosis through the β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Among these candidates, the 3′-UTR of MACC1 contains complementary binding sequences for miR-876-3 ( Figure 4G) and was chosen for further confirmation because of its wellknown oncogenic actions in TSCC progression. 33 Data from the luciferase reporter assay revealed that the upregulation of miR-876-3p strikingly reduced the luciferase activity of wt-MACC1 in SCC-15 and CAL-27 cells, whereas mutation of the binding site in MACC1 3ʹ-UTR counteracted the suppressive action of miR-876-3p on luciferase activity ( Figure 4H). Furthermore, MACC1 was clearly overexpressed in TSCC tissues than in adjacent normal tissues ( Figure 4I).…”
Section: Macc1 Is a Target Of Mir-876-3p In Tscc Cellsmentioning
confidence: 97%
“…Expression of MACC -1 gene is twofold higher in CSCs than in head and neck cancer cells and could be a biomarker for head and neck cancer [13].…”
Section: Identification and Characterization Of Cscs Vs Scsmentioning
confidence: 99%